Profit Protection Strategy And Consumer Perception Of Fairness: Testing The Dual Entitlement Principle in Indonesia - Laurentia Amadea; Harry Susianto (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
In economic psychology, the principle of Dual Entitlement asserts that buyers are entitled to reference price and sellers are entitled to reference profit. Sellers are not permitted to increase their price solely to increase their profit because such action would be deemed unfair by buyers. But what if the cost of production or operation rises, putting the reference profit at risk? Buyers will perceive it as fair when the sellers’ decision to increase their price is aimed at protecting their reference profit. Previous studies on consumer perception of fairness and profit protection have focused on price increases as sellers’ strategy to protect their reference profit. What about an alternative strategy of reducing the amount of refunds given to buyers? Does price framing, consolidated versus disaggregated, affect consumer’s fairness perception? The current experimental utilized a 2 (profit protect strategy: price increase vs. refund reduction) X 2 (price information: consolidated vs. disaggregated price) between-subject design involving 207 participants (age range 18-23 years; Median age = 19; 81% female) to examine consumer perception of fairness towards the airline’s profit protection strategy. The result showed that both increasing prices and reducing refunds were considered equally fair by participants even after controlling their perception of Indonesian sellers’ pricing practices. However, when taking price information into consideration, the disaggregated price increase was considered more fair compared to the consolidated one. Interestingly, the case wasn’t the same with refund reduction as participants perceived disaggregated price disclosure less fair than consolidated one. Implications and suggestions for further research are discussed..Dalam psikologi ekonomi, prinsip Dual Entitlement menyatakan bahwa pembeli berhak atas harga patokan dan penjual berhak atas laba patokan. Penjual tidak diperkenankan untuk menaikkan harga semata-mata untuk menambah keuntungan karena tindakan tersebut akan dipersepsikan pembeli sebagai perilaku tidak adil. Lalu bagaimana jika ongkos produksi atau operasional penjual membengkak dan laba patokan terancam? Pembeli dapat memahami tindakan penjual menaikkan harga hanya jika hal tersebut bertujuan untuk melindungi laba patokan. Studi terdahulu mengenai persepsi keadilan pembeli terhadap strategi melindungi laba berfokus pada menaikkan harga sebagai strategi utama penjual. Bagaimana dengan alternatif strategi mengurangi jumlah refund yang dikembalikan pada pembeli? Selain itu, apakah cara penjual menyajikan informasi harga secara total ataupun rinci berpengaruh pada persepsi keadilan? Eksperimen ini menggunakan desain 2 (strategi melindung laba: menaikkan harga vs. penurunan refund) X 2 (penyajian informasi harga: total vs. harga rinci) dan melibatkan 207 partisipan (rentang usia 18-23 tahun; Median usia = 19; 81% perempuan) untuk menguji persepsi keadilan pembeli terhadap strategi melindungi laba yang dilakukan oleh maskapai penerbangan. Hasilnya, baik menaikkan harga maupun pengurangan refund dengan cara penyampaian informasi harga total maupun rinci dipersepsikan sama adilnya oleh partisipan, bahkan setelah mempertimbangkan persepsi terhadap pricing practice penjual di Indonesia yang tidak adil. Namun, ketika mempertimbangkan bagaimana informasi harga disajikan, menaikkan harga dengan informasi rinci dipersepsikan lebih adil dibandingkan secara total. Menariknya, pengurangan refund secara rinci justru dipersepsikan tidak lebih adil dibandingkan secara total. Implikasi dan saran studi lanjutan dibahas dalam penelitian ini.